ANALISIS HASIL ASSESMEN DIAGNOSTIK KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA PADA PEMBELAJARAN DIMENSI TIGA TIPE TPS KELAS X - Haryanti, Sri (Universitas Muhammadiyah Semarang, 2018)
This study aims to find out: the initial ability of students mathematical communication; TPS type learning process accompanied by diagnostic analysis; analysis of student difficulties; effectiveness of TPS-type learning accompanied by diagnostic analysis; and students mathematical communication skills after TPS type learning is accompanied by diagnostic analysis. The scope of the learning material in this study is the Three Dimensions for class X students. This type of research is mixed methods with concurrent embedded research designs. Qualitative methods as primary methods, while quantitative methods as secondary methods. Samples in qualitative research were taken by purposive sampling technique. Samples in quantitative research were taken by cluster random sampling technique. The research data was collected through questionnaires and written tests. Questionnaire data were analyzed descriptively qualitatively and test data were analyzed by proportion test, Uni Anova and Gain test. The results showed that 1) The initial ability of mathematical communication of students is still below the minimum completeness criteria. Student responses are low; 2) TPS type learning process accompanied by diagnostic analysis is carried out through three stages of think-pair-share; 3) TPS type learning accompanied by effective diagnostic analysis is evident from mathematical communication that achieves completeness, increases and is significantly better than the control group; 4) The difficulty of most students is not paying attention to the notation and not being careful in calculating; 5) Students mathematical communication skills after TPS type learning accompanied by diagnostic analysis in the upper, middle and lower groups have been able to express mathematical ideas, have been able to draw according to the problems given and write mathematical notations are still lacking.